Transcriptomic profiling in canine B-cell lymphoma supports a synergistic effect of BTK and PI3K inhibitors - Lainscsek, Xenia; Kong, Weibo; Rütgen, Barbara C.; Beck, Julia; Brenig, Bertram; Nolte, Ingo; Murua Escobar, Hugo; Taher, Leila (Frontiers in Veterinary Science, 2025)
IntroductionB-cell receptor (BCR) signaling has revealed itself as a critical pathway in the pathogenesis of B-cell lymphoma. Within this pathway, the inhibition of Bruton's tyrosine kinase (BTK) or Phosphoinositide 3-kinases (PI3Ks) alone presents encouraging efficacy in the treatment of certain both canine and human hematological malignancies.MethodsHere we characterized the effects of the BTK inhibitor Ibrutinib and the PI3K inhibitor AS-605240 as single and combined agents in the canine pre-clinical diffuse large B cell lymphoma (DLBCL) model CLBL-1 by assaying cell proliferation and metabolic activity, and performing RNA-seq to measure gene expression changes.ResultsWe found 2,336 differentially expressed genes (DEGs) across all treatment types and time points relative to the control. The largest number of DEGs were induced by the combination of Ibrutinib and AS-605240. These genes were involved in adaptive immune response, leukotriene D4 metabolic and terms related to regulation of GTP and GTPase mediated signal transduction. Weighted gene co-expression network analysis (WGCNA) detected nine gene modules, five of which were associated with treatment response. Eighteen-percent of genes within these modules were also differentially expressed. Notably, we observed one module that was exclusively associated with the combined treatment whose gene members were related to cellular metabolism, homeostasis signaling, and protein synthesis and regulation.ConclusionNarrowing in on highly connected genes of modules associated with treatment response with large fold changes across treatments which play roles in the main targeted pathways identified PAG1, PRKAR2A, ACACA, FOS, and PRKCA as potential primary candidates of the synergistic treatment effect.